Climate Change Spillover Effects on Agricultural Economics: Correlating Rainfall Anomalies (ENSO) and Farmer's Terms of Trade in Indonesia - Leni Sabrina; Nurhapsa Nurhapsa; Elly Jumiati (CV. HEI PUBLISHING INDONESIA, 2026)
This study investigates the profound socioeconomic implications of precipitation variability on agricultural stability, specifically focusing on how ENSO-induced rainfall anomalies trigger economic spillover effects within the Indonesian agrarian sector. Addressing the critical intersection of climatology and macroeconomics, the research aims to quantify the correlation between meteorological shocks and the Farmer's Terms of Trade (FTT). Utilizing official secondary datasets from the Bureau of Meteorology, Climatology, and Geophysics (BMKG) and Statistics Indonesia (BPS) for the period 2021–2024, the study employs a quantitative approach integrating Pearson correlation analysis and the Vector Error Correction Model (VECM). The results demonstrate a significant positive correlation (r = .658 ; p = .003) between rainfall stability and farmer welfare, revealing a severe